2007
DOI: 10.1073/pnas.0607377104
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of 1, N 6 -ethanoadenine genotoxicity by the Escherichia coli adaptive response protein AlkB

Abstract: 1,N 6 -ethanoadenine (EA) forms through the reaction of adenine in DNA with the antitumor agent 1,3-bis(2-chloroethyl)-1-nitrosourea, a chemotherapeutic used to combat various brain, head, and neck tumors. Previous studies of the toxic and mutagenic properties of the DNA adduct EA have been limited to in vitro experiments using mammalian polymerases and have revealed the lesion to be both miscoding and genotoxic. This work explores lesion bypass and mutagenicity of EA replicated in vivo and demonstrates that E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 38 publications
2
67
1
Order By: Relevance
“…However, results from our in vitro biochemical assay suggested Aside from TET enzymes, other members of the Fe(II)-and 2-OG-dependent dioxygenase family may also act as potential molecular targets for copper toxicity. Escherichia coli AlkB protein, which is an ortholog of human ALKBH2 and ALKBH3, were shown to be capable of repairing etheno DNA lesions (46,47). Thus, compromised ALKBH repair activity arising from elevated copper content may also account, in part, for greater accumulation of etheno DNA lesions in liver tissues of LEC rats relative to LEA rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, results from our in vitro biochemical assay suggested Aside from TET enzymes, other members of the Fe(II)-and 2-OG-dependent dioxygenase family may also act as potential molecular targets for copper toxicity. Escherichia coli AlkB protein, which is an ortholog of human ALKBH2 and ALKBH3, were shown to be capable of repairing etheno DNA lesions (46,47). Thus, compromised ALKBH repair activity arising from elevated copper content may also account, in part, for greater accumulation of etheno DNA lesions in liver tissues of LEC rats relative to LEA rats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, AlkB was initially characterized as a dioxygenase resulting in the removal of the lesions 1-methyladenine and 3-methylcytosine, and its action was subsequently found to extend to 3-alkylpyrimidines and 1-alkylpurines (21,24,42). However, Essigmann and coworkers have shown that AlkB is the principal enzyme that removes 1,N 6 -ethenoadenine and 1,N 6 -ethenocytosine (20) as well as 1,N 6 -ethanoadenine (28), adducts that can result from hydroxyl radical lipid peroxidation-mediated DNA damage (25). Other glycosylases that remove oxidized bases include AlkA (7,46), MUG (37,59), KsgA (71), and endonucleases III (55,62) and VIII, encoded by the nth gene (33) and the nei gene (36,48), respectively.…”
Section: Figmentioning
confidence: 99%
“…After the initial oxidation, the exocyclic bridge can open, forming another monoalkyl lesion that either can fall apart spontaneously or is further oxidized by AlkB. For example, 1,N 6 -ethanoadenine (EA), the saturated analog of ⑀A, is completely repaired by E. coli AlkB, with the reaction involving two successive oxidation steps at the carbons on the N1 and N 6 positions of adenine (83,88). Similarly, 3,N 4 -␣-hydroxyethanocytosine (the hydrated version of ⑀C) and the three-carbon bridge analog 3,N 4 -␣-hydroxypropanocytosine are also good AlkB substrates, but require only one oxidation at the carbon attached to the N3 of cytosine (10,84).…”
Section: Exocyclic Bridge-containing Lesionsmentioning
confidence: 99%